2014
DOI: 10.5796/electrochemistry.82.267
|View full text |Cite
|
Sign up to set email alerts
|

Li Utilization and Cyclability of Li-O2 Rechargeable Batteries Incorporating a Mesoporous Pd/^|^beta;-MnO2 Air Electrode

Abstract: The effects of Li utilization on the capacity and cycle stability of Li-O 2 batteries were studied by investigating the performance of cells incorporating varying ratio of Li metal to air electrode catalyst. The quantity of Li metal was found to affect the overall discharge capacity, such that the capacity decreased with decreasing amounts of Li in the anode. Although a capacity of only 354 mAh g −1 (cathode) was obtained when the anode contained 0.9 mg Li, almost 100% of the Li in the cell was consumed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The important role played by the irreversible transformation of Li anode in the failure mechanism of LOB performance during long-term operation is thus clearly identified. Other compelling corroboration of the influential role played by Li anode has been shown by Jang et al, 53 who experimentally displayed that a new cell assembled with used cathode and new Li anode functioned properly, while a new cell assembled with a used Li anode and new cathode did not. This has also been confirmed by Schroeder et al, who found that the failed LOB can be fully recovered to the same state before failure by solely replacing the used Li anode.…”
Section: Acs Energy Lettersmentioning
confidence: 99%
“…The important role played by the irreversible transformation of Li anode in the failure mechanism of LOB performance during long-term operation is thus clearly identified. Other compelling corroboration of the influential role played by Li anode has been shown by Jang et al, 53 who experimentally displayed that a new cell assembled with used cathode and new Li anode functioned properly, while a new cell assembled with a used Li anode and new cathode did not. This has also been confirmed by Schroeder et al, who found that the failed LOB can be fully recovered to the same state before failure by solely replacing the used Li anode.…”
Section: Acs Energy Lettersmentioning
confidence: 99%